Functionalized Lanthanide Oxide Nanoparticles for Tumor Targeting, Medical Imaging, and Therapy - Mohammad Yaseen Ahmad; Huan Yue; Tirusew Tegafaw; Shuwen Liu; Son Long Ho; Gang Ho Lee; Sung-Wook Nam; Yongmin Chang (Pharmaceutics, 2021)
Recent progress in functionalized lanthanide oxide (Ln2O3) nanoparticles for tumor targeting, medical imaging, and therapy is reviewed. Among the medical imaging techniques, magnetic resonance imaging (MRI) is an important noninvasive imaging tool for tumor diagnosis due to its high spatial resolution and excellent imaging contrast, especially when contrast agents are used. However, commercially available low-molecular-weight MRI contrast agents exhibit several shortcomings, such as nonspecificity for the tissue of interest and rapid excretion in vivo. Recently, nanoparticle-based MRI contrast agents have become a hot research topic in biomedical imaging due to their high performance, easy surface functionalization, and low toxicity. Among them, functionalized Ln2O3 nanoparticles are applicable as MRI contrast agents for tumor-targeting and nontumor-targeting imaging and image-guided tumor therapy. Primarily, Gd2O3 nanoparticles have been intensively investigated as tumor-targeting T1 MRI contrast agents. T2 MRI is also possible due to the appreciable paramagnetic moments of Ln2O3 nanoparticles (Ln = Dy, Ho, and Tb) at room temperature arising from the nonzero orbital motion of 4f electrons. In addition, Ln2O3 nanoparticles are eligible as X-ray computed tomography contrast agents because of their high X-ray attenuation power. Since nanoparticle toxicity is of great concern, recent toxicity studies on Ln2O3 nanoparticles are also discussed.